Pengembangan Kurikulum Bahasa Arab pada Masa Pandemi Covid-19 dalam Menjawab Tantangan Era Society 5.0 - Rahman, Fathor; Hasyim Asy'ari; Elifatul Zazil (Lembaga Penelitian, Pengabdian kepada Masyarakat dan Publikasi Ilmiah (LP3M) Institut Agama Islam (IAI) Al-Qodiri Jember, Jawa Timur Indonesia bekerjasama dengan Kopertais Wilayah 4 Surabaya, 2024)
This study aims to uncover the concept of Arabic language curriculum development at the Al-Qodiri 1 Junior High School (Mts Unggulan) in Jember during the pandemic and post-pandemic periods. The research method used in this study employs a qualitative approach with a field study type. The findings of this study reveal, first, the concept and implementation of learning adapted to government policies in response to the COVID-19 pandemic, which is digital-based. The concept of Arabic language learning during the COVID-19 pandemic to address the challenges of the 5.0 era at Mts Unggulan Al-Qodiri is designed in accordance with the characteristics of the Arabic language learning process. In line with the policy from the Ministry of Education and Culture to conduct online learning, the learning concept during the pandemic is implemented through the delivery of materials using e-modules, PowerPoint presentations (PPT), YouTube videos, face-to-face sessions via Zoom, Skype, Hangouts Meet, Google Meet, and WhatsApp groups. The content is delivered through WhatsApp groups, Google Classroom, Telegram, Line, and the forum feature in LMS. Second, the strategy used in Arabic language learning is adjusted to the limitations imposed by the pandemic, which restricts face-to-face interaction and gatherings. Therefore, the strategy for the duration of learning is conducted online by utilizing online learning media such as Zoom, Skype, Hangouts Meet, Google Classroom, and WhatsApp groups.